HUBUNGAN STRES TERHADAP SIKLUS MENSTRUASI PADA SISWI PONDOK PESANTREN PUTRI UMMU SULAIM PEKANBARU TAHUN 2018 - Andriani Ummu Khalishah (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Background: Menstrual cycle is the time since the first day of menstruation until the arrival of next menstrual period. Menstrual cycle ideally regular every month with a span of time between 21 to 35 days each time the menstrual period and menstrual cycle can vary in women during different times of life depending on various things, one of which in the stress factor. In it’s effect on the menstrual cycle, stress involves the neoro-endocrinological system as a large system of it’s role in female reproduction. This menstrual cycle disorder involves an integrative regulatory mechanism that affects the body biochemical and cellular processes including the brain and psychological. Purpose: The pupose of this study was determine the relationship of stress to the menstrual cycle for students of Islamic Boarding School of Ummu Sulaim Pekanbaru Year 2018. Method: This research uses quantitative analytic research type, with cross sectional design using questionnaire as a measuring tool as well as sampling was stratified random sampling. Results: The results of this study indicate that moderate stress with irregular menstrual cycles that have equal to 57,1% p value 0,001 > ? 0,005 means there is a relationship of stress to the menstrual cycle on students. Conclusion: The researcher’s suggestion is expected for students of Islamic Boarding School of Ummu Sulaim Pekanbaru in order to make good time management so that all activities, duties and memorization do not accumulate so it does not become burden which make student stress and consequently will affect the cycle of menstruation.Keyword : Stres, Menstrual cycle